PENGEMBANGAN MATERI AJAR PRODUKSI LISAN BERBASIS MICROLEARNING BAGI GURU BAHASA DI KABUPATEN AGAM, SUMATERA BARAT, INDONESIA - Siti Drivoka Sulistyaningrum; Ifan Iskandar; Ratna Dewanti (IKIP Siliwangi Bandung, 2022)
The microlearning method has been accelerating and facilitating the pedagogical approach to developing teachers as professionals in 21st-century learning. However, research intoÂ English speaking learning materials, particularly microlearning-based English speaking learning materials for the teachers in Agam District, West Sumatra, is limited and urged. This study reports the development of Common European Framework (CEFR) and microlearning-based spoken production learning materials for teachers of junior high schools in Agam through the workshop. The findings revealed that the teachersâ€™ competence was significantly positive in developing learning materials based on microlearning. They become skillful and able to design microlearning-based English-spoken materials for their context and their needs. Their expertise can have an impact on the teachers in Agam and act as a socializing agent for the other teachers in West Sumatra